Sarcopenic obesity in the ICU. Issue 2 (March 2019) - Tieland, Michael; van Dronkelaar, Carliene; Boirie, Yves
Abstract : Purpose of review: Sarcopenic obese in older ICU patients may have a higher risk of poor recovery during and after ICU stay, which may lead to longer hospital stay and poor quality of life. In this review, causes, consequences, and nutrition strategies to combat sarcopenic obesity in the ICU are discussed. Recent findings: Physical inactivity, inflammation, anabolic resistance, as well as disturbances in hormone levels are, important causes for the strongly accelerated decline in muscle mass and muscle strength in ICU patients. These causes may lead to changes in amino acid metabolism and anabolic resistance. Obese individuals show specific muscle characteristics (e.g. adipose infiltration, lower capillary density) which are associated with impaired functionality. Specific energy and protein intake recommendations are needed to attenuate sarcopenic obesity in ICU patients. Summary: Nutrient utilization in sarcopenic obese ICU patients is a complex challenge as many metabolic factors and clinical situations may impact the efficacy of nutritional interventions. Nutritional strategies should consist of high-protein and hypocaloric feeding along with nonprotein sources such as vitamin D, omega-3 fatty acids, or physical activity. There is a great need, however, for randomized controlled trials (RCTs) combining various nutritional strategies with physical activity in sarcopenic obese ICU patients.